Opinion on the re‐evaluation of acacia gum (E 414) as a food additive in foods for infants below 16 weeks of age and the follow‐up of its re‐evaluation as a food additive for uses in foods for all population groups. (13th December 2019) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gürtler, Rainer; Husøy, Trine; Mennes, Wim; Moldeus, Peter; et al.
Abstract: EFSA is re‐evaluating the safety of food additives already permitted in the Union before 20 January 2009 and issuing scientific opinions on their safety in line with Regulation (EC) No 1333/2008. Acacia gum (E 414) was re‐evaluated in 2017 by the former EFSA Panel on Food Additives and Nutrient sources added to Food (ANS). As follow‐up to this assessment, the Panel on Food Additives and Flavourings (FAF) was requested to assess the safety of acacia gum (E 414) as carry‐over in food for infants below 16 weeks of age belonging to food categories 13.1.1 (Infant formulae) and 13.1.5.1 (Dietary foods for infants for special medical purposes and special formulae for infants) and to address the issues already identified during the re‐evaluation of the food additive when used in food for the general population. The process involved the publication of a call for data to allow the interested parties to provide the requested information to complete the risk assessment. Based on the analytical data submitted in response to this call, the Panel recommended to lower the limits in the specifications for toxic elements and identified the need for further specifications for aluminium, microbiological criteria and protein residues. The Panel noted that information was not provided for oxidising enzymes and recommended that oxidases and peroxidases should be inactivated during the manufacturing process. The interested parties did not submit toxicological, clinical and post‐marketing surveillance data specific for the assessment of the safety of acacia gum (E 414) in infants below 16 weeks of age. However, taking the highest doses tested without adverse effects from the subchronic studies available from the previous re‐evaluation and comparing them with the estimated exposure in infants, the margins of safety were large indicating that there is no reason for health concern.